Analisis Penilaian Persediaan Beras dengan Metode FIFO, FEFO, dan Average untuk Menentukan Harga Pokok Penjualan di UD. Rahayu Indah - Ida Wahyuni; Faisol Faisol; Sigit Puji Winarko (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze and compare rice inventory valuation using the FIFO, FEFO, and Average methods in determining the cost of goods sold (COGS) at UD. Rahayu Indah. This study uses a quantitative descriptive approach with a perpetual inventory recording system. Data were collected through observation, interviews, and documentation from January to December 2024. The results show that each method produces different COGS values: the FIFO method produces the lowest COGS, followed by FEFO, while the Average method produces the highest COGS. This difference is influenced by cost allocation based on the order of goods in and out and price fluctuations during the production period. These findings indicate that the FIFO method is the most effective method to be applied at UD. Rahayu Indah because it reflects the logical physical flow of goods, supports cost efficiency, and increases the company's gross profit. In addition, this method is also in line with the company's operational characteristics, which have stable purchasing patterns and are in accordance with the principles of PSAK No. 14 on inventory. The results of this study are expected to assist UD. Rahayu Indah's management in determining an inventory valuation strategy that is efficient, accurate, and supports business sustainability.